Sexuality and Religion in Late Francoism. The Reception of Humanae Vitae in Spain and the Crisis of Authority in the Church - García Fernández, Mónica (Hispania Nova, 2021)
This paper analyses the context of Paul VI’s encyclical Humanae Vitae (1968) and its reception in Spain. The aim is to explore its background debates and impact in relation to the Second Vatican Council and also to the so-called “disengagement” of the Church from the Franco Regime in its final years. The controversy that surrounded the document put into question the Church’s moral authority. Furthermore, it is understood in the context of a substantial change in the catholic definition of sexuality. This is also linked to a heated debate about birth control in which the popularization of the “pill” had a significant influence.